Biodegradation of the Ciprofloxacin Antibiotic by White Rot Fungus Trametes hirsuta D7 - Ananda Novita Hi Pattu; Charlena Charlena; Dede Heri Yuli Yanto; Irma Herawati Suparto; Maulida Oktaviani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
This study highlights the potential of fungal microorganisms, particularly Trametes hirsuta D7, in addressing antibiotic contaminants, such as ciprofloxacin, in the environment. The degradation process was conducted at room temperature over 7 days, and the results demonstrated that laccase was predominant in the degradation capacity; this was evidenced by the laccase enzyme activity levels obtained, namely 93 U/L, 120 U/L, and 130 U/L, compared to manganese peroxide activity of 7 U/L, 16 U/L, and 13 U/L at concentrations of 100, 300, and 500 mg/L, respectively. Notably, the laccase enzyme of T. hirsuta D7 exhibited significant degradation of ciprofloxacin, with high degradation rates of 64% at 100 mg/L, 48% at 300 mg/L, and 26% at 300 mg/L. This indicates that laccase from T. hirsuta D7 effectively degraded ciprofloxacin at various concentrations. Furthermore, this study revealed that ciprofloxacin did not significantly affect the growth of T. hirsuta D7. This suggests that microorganisms can survive and function effectively in the presence of antibiotic contamination without being impaired by these compounds. In conclusion, this study presents a potential solution for environmental antibiotic contamination by utilizing fungal microorganisms, particularly T. hirsuta D7, and their laccase enzymes. The findings of this study provide valuable insights for developing more environmentally sustainable and efficient degradation methods for antibiotic contamination in the ecosystem.